2017
DOI: 10.1038/s41588-017-0015-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of H3K4me1-associated proteins at mammalian enhancers

Abstract: Enhancers act to regulate cell type specific gene expression by facilitating the transcription of target genes. In mammalian cells active or primed enhancers are commonly marked by monomethylation of Histone H3 at lysine 4 (H3K4me1) in a cell-type specific manner. Whether and how this histone modification regulates enhancer-dependent transcription programs in mammals is unclear. In this study, we conducted SILAC Mass-spec experiments with mono-nucleosomes and identified multiple H3K4me1 associated proteins, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
180
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 214 publications
(203 citation statements)
references
References 62 publications
17
180
0
Order By: Relevance
“…As we did not observe consistent associations between PSP-associated MAPT intron 1 variants with either LRRC37A/2 copy number and expression, or MAPT expression and splicing, we examined ATAC-seq data and publicly available epigenetic data in order to determine the likely functional impact of rs8076152 and H1c variants. Analysis of publicly available ChIP-seq data (Roadmap Epigenetics Consortium 47 ) reveals that rs242557 lies within a region enriched for H3K27ac, H3K4me1and H3K9ac marks in brain tissue (Fig 5A, SI Table 10), which is consistent with the presence of an active enhancer region in this locus [48][49][50] . The second PSP-associated variant, rs8076152, is also within a brain-specific weak enhancer region (Fig 5A, SI Table 10).…”
Section: Psp-associated Mapt Intronic Variants Alter Chromatin Structmentioning
confidence: 52%
“…As we did not observe consistent associations between PSP-associated MAPT intron 1 variants with either LRRC37A/2 copy number and expression, or MAPT expression and splicing, we examined ATAC-seq data and publicly available epigenetic data in order to determine the likely functional impact of rs8076152 and H1c variants. Analysis of publicly available ChIP-seq data (Roadmap Epigenetics Consortium 47 ) reveals that rs242557 lies within a region enriched for H3K27ac, H3K4me1and H3K9ac marks in brain tissue (Fig 5A, SI Table 10), which is consistent with the presence of an active enhancer region in this locus [48][49][50] . The second PSP-associated variant, rs8076152, is also within a brain-specific weak enhancer region (Fig 5A, SI Table 10).…”
Section: Psp-associated Mapt Intronic Variants Alter Chromatin Structmentioning
confidence: 52%
“…While little is known about the function of remodeling complexes in CLL, the NuRD and SWI/SNF remodelers play an important role in hematopoiesis and differentiation and have been implicated in oncogenesis and cancer progression in numerous other entities (Lai & Wade, ; Kadoch & Crabtree, ; Prasad et al , ). Furthermore, it is noted that the ability of these complexes to translocate nucleosomes might be crucial to modulate chromatin accessibility at enhancers and involve their targeting by histone modifications like H3K4me1 (Local et al , ). In line with these considerations, we observe striking changes in nucleosome positioning and occupancy at B‐cell‐specific genes in CLL.…”
Section: Discussionmentioning
confidence: 99%
“…Although H3K4me1 is the predominant mark of a primed enhancer state, it is unclear whether H3K4me1 affects or simply correlates with enhancer activation in cell differentiation and development. Interestingly, the latest two studies from one group reported that MLL3/4-dependent H3K4me1 has an active role at enhancers by facilitating binding of the chromatin remodeler SWI/SNF complex and recruitment of the chromatin organization regulator cohesin complex to orchestrate long-range chromatin interactions in ES cells 20,21 . These findings imply that H3K4me1 is not simply a correlative outcome in enhancer regulation.…”
Section: Discussionmentioning
confidence: 99%